Selective Synthesis of Unsymmetrical Diboryl PtII and Diaminoboryl CuI Complexes by B–B Activation of Unsymmetrical Diboranes(4) {pinB–B[(NR)2C6H4]}. Issue 15 (23rd April 2014) - Borner, Corinna; Kleeberg, Christian
Abstract: Diaminoboryl ligands are currently intensively investigated because of their unique coordination chemical properties, for example, as part of pincer ligands. Owing to synthetic restrictions, however, access to diaminoboryl complexes is limited. Unsymmetrical diborane(4) derivatives comprising a dialkoxy‐ and a diaminoboron moiety provide efficient access to diaminoboryl complexes either by oxidative addition or by σ‐bond metathesis reactions. Especially, the latter is complementary to existing methods and overcomes the existing limitations. This is illustrated by the modular synthesis of four unsymmetrical diborane(4) derivatives and their application in the selective preparation of unprecedented unsymmetrical diboryl Pt II complexes as well as sterically little encumbered diaminoboryl Cu I complexes. Abstract : Unsymmetrical diboranes(4) of the type {pinB–B[(NR)2 C6 H4 ]} are used as precursors for the selective synthesis of unprecedented unsymmetrical Pt II diboryl and diaminoboryl Cu I complexes by oxidative addition and σ‐bond metathesis reactions, respectively. A versatile and modular route to the unsymmetrical diborane(4) compounds used is described; pin = pinacolato, Dipp = 2, 6‐diisopropylphenyl, IDipp = 1, 3‐bis(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene.